2018
DOI: 10.1111/puar.12996
|View full text |Cite
|
Sign up to set email alerts
|

Equity or Efficiency? Explaining Public Officials' Values

Abstract: This article analyzes the positions of top public officials on an equity‐efficiency trade‐off and the determinants of those positions. It uses data from a survey across 14 European countries. The results show that differences in public officials' positions on equity‐efficiency are related to the context in which they work and to their personal background. Officials at the top of the hierarchy and those with a business or economics education are more oriented toward efficiency. Additionally, results show import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 55 publications
0
39
0
2
Order By: Relevance
“… The COCOPS Executive Survey data set is used, for example, in Fernández‐Gutiérrez and Van de Walle (); George, Van de Walle, and Hammerschmid (); Hammerschmid et al (); Jeannot, Van de Walle, and Hammerschmid (); Lapuente, Suzuki, and Van de Walle (); Suzuki and Hur (); and Van der Voet and Van Walle (). The QoG Expert Survey is used, for example, in Charron, Dahlström, and Lapuente (); Cornell (); Cornell and Grimes (); Dahlström and Lapuente (); Nistotskaya and Cingolani (); Schuster (, ); and Suzuki and Demircioglu ().…”
mentioning
confidence: 99%
“… The COCOPS Executive Survey data set is used, for example, in Fernández‐Gutiérrez and Van de Walle (); George, Van de Walle, and Hammerschmid (); Hammerschmid et al (); Jeannot, Van de Walle, and Hammerschmid (); Lapuente, Suzuki, and Van de Walle (); Suzuki and Hur (); and Van der Voet and Van Walle (). The QoG Expert Survey is used, for example, in Charron, Dahlström, and Lapuente (); Cornell (); Cornell and Grimes (); Dahlström and Lapuente (); Nistotskaya and Cingolani (); Schuster (, ); and Suzuki and Demircioglu ().…”
mentioning
confidence: 99%
“…In a recent study about the values of public officials (not only in the health system), authors found that tensions between values and value trade-offs are frequently founded in the public sector, principally when the decision-making imply allocation and redistribution of resources. 33 In the analysis about the trade-off between efficiency and equity, authors suggest that public officials closer to the recipients of policies, are more pro-equity oriented, while public officials that have been exposed to private sector management, are more proefficiency oriented. 33 Our results are consistent with those of Fernández-Gutiérrez and Van de Walle, 33 but highlight a new actor as policy-maker, the judiciary sector.…”
Section: Discussionmentioning
confidence: 99%
“…33 In the analysis about the trade-off between efficiency and equity, authors suggest that public officials closer to the recipients of policies, are more pro-equity oriented, while public officials that have been exposed to private sector management, are more proefficiency oriented. 33 Our results are consistent with those of Fernández-Gutiérrez and Van de Walle, 33 but highlight a new actor as policy-maker, the judiciary sector. In our study, interviewees from the executive branch were more oriented to prioritize financial sustainability and efficiency, while interviewees from the judiciary branch were more oriented to human dignity and equity.…”
Section: Discussionmentioning
confidence: 99%
“…Top civil servants constantly have to balance different values in their work and are often confronted with value conflicts (De Graaf, Huberts, & Smulders, 2016). Especially in situations where decision-making is concerned with budget allocation, tensions between conflicting values (such as efficiency and equity) can arise (Okun, 1975;Fernandez-Gutiérrez & Van de Walle, 2018). This particularly holds when resources become scarce, as is the case during cutbacks.…”
Section: Cutback Management; éLite Interviews; Top Civil Servants; Vamentioning
confidence: 99%